2018
DOI: 10.1098/rspb.2017.2688
|View full text |Cite
|
Sign up to set email alerts
|

Strong linkages between depth, longevity and demographic stability across marine sessile species

Abstract: Understanding the role of the environment in shaping the evolution of life histories remains a major challenge in ecology and evolution. We synthesize longevity patterns of marine sessile species and find strong positive relationships between depth and maximum lifespan across multiple sessile marine taxa, including corals, bivalves, sponges and macroalgae. Using long-term demographic data on marine sessile and terrestrial plant species, we show that extreme longevity leads to strongly dampened population dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 56 publications
(68 reference statements)
1
28
0
1
Order By: Relevance
“…We expect that our observed patterns will apply to similar habitats beyond our study area because longevity is a fundamental life history trait, which will be under selection from the environmental conditions characteristic for a particular habitat (Montero‐Serra et al. ). Comparison of the range in habitats represented in our benthic data set with the range observed in the North Sea area shows that our data is biased to areas shallower than 150 m (Appendix ).…”
Section: Discussionmentioning
confidence: 92%
“…We expect that our observed patterns will apply to similar habitats beyond our study area because longevity is a fundamental life history trait, which will be under selection from the environmental conditions characteristic for a particular habitat (Montero‐Serra et al. ). Comparison of the range in habitats represented in our benthic data set with the range observed in the North Sea area shows that our data is biased to areas shallower than 150 m (Appendix ).…”
Section: Discussionmentioning
confidence: 92%
“…We did not attempt to model the variance around normal growth rates due to the extremely low variance around mean growth. While this is a simplification, our previous work has shown that red coral population growth has relatively low sensitivity to growth rates, which likely minimizes any effects of this modelling decision (Montero‐Serra, Linares, Doak, Ledoux, & Garrabou, ).…”
Section: Methodsmentioning
confidence: 99%
“…The adverse impact of fishing to vulnerable marine ecosystems, such as cold‐water coral (CWC) reefs and coral gardens (OSPAR Commission, ) and the need to conserve them, have become a global concern (Angiolillo & Canese, ; Davies, Roberts, & Hall‐Spencer, ). Owing to the low resilience of coral garden species, they display high vulnerability to disturbance from human activities (Montero‐Serra, Linares, Doak, Ledoux, & Garrabou, ; Roberts & Hirshfield, ), which has prompted a growing interest in protection and restoration initiatives aimed at mitigating their further degradation and enhancing their recovery (Angiolillo & Canese, ). Currently, a few deep‐sea active restoration initiatives have mainly focused on transplantation actions of CWC species, such as Oculina varicosa off the south‐eastern coast of Florida (Brooke et al, ) and Lophelia pertusa in Sweden (Dahl, ).…”
Section: Introductionmentioning
confidence: 99%